Reaction mechanism and reservoir simulation study of the high-temperature nitrogen injection in-situ oil shale process: A case study in Songliao Basin, China. (15th May 2022) - Zhu, Chaofan; Guo, Wei; Sun, Youhong; Li, Qiang; Deng, Sunhua; Wang, Yuan; Cui, Guodong
Highlight: An numerical simulation based on the pilot project in Songliao Basin was conducted to analyse the HNICP. The oil production rate can be divided into four stages for the HNICP. The formation plugging in the low TOC shale formation is more serious. The small enclosing area is beneficial to the production of oil. Abstract: China's oil shale reserves are 739.1 billion tons and 45 per cent of which are in Songliao Basin. Therefore, a pilot project is conducted in Songliao Basin, aimed at technical preparation for commercial in-situ oil shale processes production. Because N2 is readily accessible and has no damage to the formation, the high-temperature nitrogen injection in-situ conversion process (HNICP) is the most basic convection heating technique, which is used in the pilot project. In this study, the Wellington reaction model is adjusted to describes the pyrolysis behavior and characteristics of shale in Songliao Basin, China. Based on the geological data and production date of the pilot project in Songliao Basin, a simulation model matching the production test scheme is established to investigate subsequent production performance and the evolution of reservoir physical properties for 550 days. Finally, the effect of injection temperature, total organic carbon (TOC), and enclosing area on the recovery factor is analyzed. The results show that the oil production rate can be divided into four stages for the HNICP of oil shale. In the third stage, prechar accumulation is very severe in the main fracture. However, the prechar accumulation relieves the heat short problem in the main fracture. The high temperature is beneficial to the production of oil, HC, and prechar. The formation plugging in the low TOC shale formation is more serious. Because of the spontaneous imbibition of oil in the formation away from the main fracture, the small enclosing area is beneficial to the production of oil.